The Week‐End Effect in Common Stock Returns: The International Evidence - JAFFE, JEFFREY; WESTERFIELD, RANDOLPH (Journal of Finance, 1985)
ABSTRACT This paper examines the daily stock market returns for four foreign countries. We find a so‐called “week‐end effect” in each country. In addition, the lowest mean returns for the Japanese and Australian stock markets occur on Tuesday. The remainder of the paper answers four questions. Are seasonal patterns in foreign stock markets independent of those previously reported in the U.S.? Do Japan and Australia exhibit a seasonal one day out of phase due to different time zones? Do settlement procedures across countries bias week‐end effects? Does the seasonal pattern in foreign exchange offset the week‐end effect in stocks for Americans investing overseas?